2017
DOI: 10.1136/vr.104075
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hyopneumoniaevaccination at or shortly before weaning under field conditions: a randomised efficacy trial

Abstract: This study assessed the efficacy of two different Mycoplasma hyopneumoniae vaccination programmes in relation to the time of weaning. Eight hundred and twenty-eight piglets were randomly divided into three groups: group V1 was vaccinated three days before weaning, group V2 at weaning (21 days of age) and group NV was left non-vaccinated. Vaccinations were performed using Ingelvac MycoFLEX. After the nursery period, 306 pigs were allocated to fattening unit (F1) and 501 pigs to a second unit (F2). Efficacy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Last but not least, the present study, together with other studies that focused at the breeding sow level, used n‐PCR for detecting the presence of the pathogen in the selected sows and their piglets, 7 8 13 18 32 and not quantitative real‐time PCR techniques. The latter techniques have been used though only in studies that focused at the fattening pig level and have shown that vaccinated pigs had a significantly reduced number of M. hyopneumoniae organisms in their lungs compared with the non‐vaccinated pigs 36 37 . For that reason, future studies investigating the effect of sow vaccination in piglet colonisation, apart from including sows of different parities, they should also employ quantitative real‐time PCR techniques for detecting the presence of M hyopneumoniae in both the samples obtained from the sows and their piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, the present study, together with other studies that focused at the breeding sow level, used n‐PCR for detecting the presence of the pathogen in the selected sows and their piglets, 7 8 13 18 32 and not quantitative real‐time PCR techniques. The latter techniques have been used though only in studies that focused at the fattening pig level and have shown that vaccinated pigs had a significantly reduced number of M. hyopneumoniae organisms in their lungs compared with the non‐vaccinated pigs 36 37 . For that reason, future studies investigating the effect of sow vaccination in piglet colonisation, apart from including sows of different parities, they should also employ quantitative real‐time PCR techniques for detecting the presence of M hyopneumoniae in both the samples obtained from the sows and their piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Single vaccination at either 7 or 21 days of age was efficacious in a pig herd with clinical respiratory disease during the second half of the fattening period (Del Pozo Sacristan et al., ). Recent experimental (Arsenakis et al., ) and field studies (Arsenakis et al., ) showed that vaccinating piglets 3 days prior to weaning conferred slightly better results than vaccination at weaning, possibly because of less interference of weaning stress.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…M. hyopneumoniae potentiates the severity of Betaarterivirus suid 1 (International Committee on Taxonomy of Viruses (ICTV, 2019), formerly named porcine reproductive and respiratory syndrome virus (PRRSV) (Thacker et al, 1999;Marois-Créhan et al, 2020), and porcine circovirus type 2 (PCV2) associated pneumonia in pigs (Seo et al, 2014;Marois-Créhan et al, 2020). Commercial vaccines are available but do not prevent colonisation of the respiratory tract (Maes et al, 2008;Arsenakis et al, 2017). Consequently antimicrobial agents are often needed to treat and help control infections (Maes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%